2011
DOI: 10.1097/dad.0b013e3181f3dba3
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Activity Within Dermal Melanocytes of Benign Melanocytic Nevi: A Study of 100 Cases With Clinical Follow-up

Abstract: It is generally accepted that otherwise benign intradermal or compound melanocytic nevi may show mitotic activity within dermal melanocytes. However, it is not known whether there is any clinical significance to this finding. Our objective is to analyze and describe the clinicopathologic features of benign nevi with mitotic activity (NMA). To do this, we collected 100 consecutive NMA during the usual course of business in our private dermatopathology practice. These cases were seen between the years 2000 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In humans, this may contribute to the recognized risk of nevi for progression to melanoma and reports that ∼25% of melanomas arise from a preexisting nevus (14,15). Underscoring the possible link between Wnt and neoplastic progression of nevi, we find that Wnt signaling is preferentially active in the least mature, more proliferative component of the nevus that appears to be of greater malignant potential (43)(44)(45). Recently, we also reported that nevus maturation is associated with marked changes in nuclear chromatin structure (55).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In humans, this may contribute to the recognized risk of nevi for progression to melanoma and reports that ∼25% of melanomas arise from a preexisting nevus (14,15). Underscoring the possible link between Wnt and neoplastic progression of nevi, we find that Wnt signaling is preferentially active in the least mature, more proliferative component of the nevus that appears to be of greater malignant potential (43)(44)(45). Recently, we also reported that nevus maturation is associated with marked changes in nuclear chromatin structure (55).…”
Section: Discussionmentioning
confidence: 79%
“…3B) (43,44). Maturation is associated with enhanced proliferation arrest because nevi can contain some mitotic cells, typically in the least mature upper portion of the nevus (45). Most important, maturation is an indicator of reduced malignant potential (43,44).…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7] Multiple mitotic figures within a single nevus were always distributed far from one another and were most often found in CMN in superficial locations. A further 19.5% of mitotically active cases, or 1.5% of all nevi, contained more than one mitotic figure, highlighting the potential for multiple mitotic figures in otherwise banal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Reported rates in these studies have varied from 0% to 19.5%, reflecting a wide variation in methodology and inclusion criteria. [1][2][3][4][5][6][7] Reported rates in these studies have varied from 0% to 19.5%, reflecting a wide variation in methodology and inclusion criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative assessments were used to derive a prognostic factor (PF) following PF = M* tumor thickness where M represented the number of mitosis per mm 2 [53]. More recently, a revival of mitosis interest emerged in CMM [5456] and in melanocytic nevi as well [57]. Currently, it is possible to highlight mitoses using immunohistochemistry directed to specific M -associated histones.…”
Section: Cmm Phase Indexesmentioning
confidence: 99%